Superior Mesenteric Artery Syndrome: Clinical, Endoscopic, and Radiological Findings - Emanuele Sinagra; Dario Raimondo; Domenico Albano; Valentina Guarnotta; Melania Blasco; Sergio Testai; Marta Marasà; Vincenzo Mastrella; Valerio Alaimo; Valentina Bova; Giovanni Albano; Dario Sorrentino; et al. (Gastroenterology Research and Practice)
Background. The superior mesenteric artery (SMA) syndrome is a rare entity presenting with upper gastrointestinal tract obstruction and weight loss. Studies to determine the optimal methods of diagnosis and treatment are required. Aims and Methods. This study aims at analyzing the clinical presentation, diagnosis, and management of SMA syndrome. Ten cases of SMA syndrome out of 2074 esophagogastroduodenoscopies were suspected. A contrast-enhanced computed tomography (CECT) scan was performed to confirm the diagnosis. After, a gastroenterologist and a nutritionist personalized the therapy. Furthermore, we compared the demographical, clinical, endoscopic, and radiological parameters of these cases with a control group consisting of 10 cases out of 2380 EGDS of initially suspected (but not radiologically confirmed) SMA over a follow-up 2-year period (2015-2016). Results. The prevalence of SMA syndrome was 0.005%. Median age and body mass index were 23.5 years and 21.5 kg/m2, respectively. Symptoms developed between 6 and 24 months. Median aortomesenteric angle and aorta-SMA distance were 22 and 6 mm, respectively. All patients improved on conservative treatment. In our series, a marked (>5 kg) weight loss (p=0.006) and a long-standing presentation (more than six months in 80% of patients) (p=0.002) are significantly related to a diagnosis of confirmed SMA syndrome at CECT after an endoscopic suspicion. A “resembling postprandial distress syndrome dyspepsia” presentation may be helpful to the endoscopist in suspecting a latent SMA syndrome (p=0.02). The narrowing of both the aortomesenteric angle (p=0.001) and the aortomesenteric distance (p<0.001) was significantly associated with the diagnosis of SMA after an endoscopic suspicion; however, the narrowing of the aortomesenteric distance seemed to be more accurate, rather than the narrowing of the aortomesenteric angle. Conclusion. SMA syndrome represents a diagnostic and therapeutic challenge. Our results show the following findings: the importance of the endoscopic suspicion of SMA syndrome; the preponderance of a long-standing and chronic onset; a female preponderance; the importance of the nutritional counseling for the treatment; no need of surgical intervention; and better diagnostic accuracy of the narrowing of the aorta-SMA distance. Larger prospective studies are needed to clarify the best diagnosis and management of the SMA syndrome.